2020
DOI: 10.3390/f11090988
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Land Use and Land Cover Changes in the Direct Influence Zone of the Braço Norte Hydropower Complex, Brazilian Amazonia

Abstract: Over the decades, hydropower complexes have been built in several hydrographic basins of Brazil including the Amazon region. Therefore, it is important to understand the effects of these constructions on the environment and local communities. This work presents a land use and land cover change temporal analysis considering a 33-year period (1985–2018) in the direct influence zone of the Braço Norte Hydropower Complex, Brazilian Amazonia, using the Collection 4.1 level 3 of the freely available MapBiomas datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The negative impacts were those that arose through the deforestation of native vegetation with human interference in the successional process [49,50]. This impact was verified between the forest -> deforestation -> pasture -> bare soil -> agriculture transition, and between the SSI -> bare soil or SSI -> agriculture class.…”
Section: Paths and Trends Of Colonisationmentioning
confidence: 81%
“…The negative impacts were those that arose through the deforestation of native vegetation with human interference in the successional process [49,50]. This impact was verified between the forest -> deforestation -> pasture -> bare soil -> agriculture transition, and between the SSI -> bare soil or SSI -> agriculture class.…”
Section: Paths and Trends Of Colonisationmentioning
confidence: 81%
“…They presented a temporal analysis of LULC change over a 33-year period (1985-2018) within the influence zone of the Braço Norte Hydropower Complex, Brazilian Amazon, using the Collection 4.1 level 3 LULC maps of the freely available MapBiomas dataset. Their findings showed that the most impacted LULC during this period was forest formation (from 414 km 2 to 287 km 2 , a reduction of In Guerrero et al [11], the authors pointed to another important factor related to the devastation of pristine, protected areas. They presented a temporal analysis of LULC change over a 33-year period (1985-2018) within the influence zone of the Braço Norte Hydropower Complex, Brazilian Amazon, using the Collection 4.1 level 3 LULC maps of the freely available MapBiomas dataset.…”
mentioning
confidence: 90%
“…Future work must link climate and other non-deforestation drivers to further elucidate the factors contributing to dangerous pollution emissions from biomass burning in Amazonia. In Guerrero et al [11], the authors pointed to another important factor related to the devastation of pristine, protected areas. They presented a temporal analysis of LULC change over a 33-year period (1985-2018) within the influence zone of the Braço Norte Hydropower Complex, Brazilian Amazon, using the Collection 4.1 level 3 LULC maps of the freely available MapBiomas dataset.…”
mentioning
confidence: 99%
“…These drivers have synergistic interactions among themselves and, when acting together, can amplify each other's impacts (Costa et al 2011;Anderson et al 2018;Athayde et al 2019;Castello and Macedo 2016;Silva et al 2019). The construction of dams, for example, inevitably results in the construction of roads, which in turn may increase deforestation for pasture and commodity crops such as soy (Fearnside 1989;Guerrero et al 2020). These land-use changes ultimately result in the pollution of rivers and streams, be it from the large-scale use of fertilizers and agricultural chemicals, the formation of toxic methylmercury in reservoirs, or rapid population growth from migration spurred by dam construction.…”
Section: Introductionmentioning
confidence: 99%